2000
DOI: 10.2136/sssaj2000.641201x
|View full text |Cite
|
Sign up to set email alerts
|

Root‐Derived Carbon and the Formation and Stabilization of Aggregates

Abstract: It is hypothesized that particulate organic matter (POM) contributes to aggregate stability. However, little is known about the dynamics of the POM fraction or its role in aggregate formation. A simulated no‐till study was conducted to examine changes in free and aggregate‐associated POM during the decomposition of in situ 14C‐labeled roots during a 1‐yr incubation in a loess‐derived silt loam. Two water pretreatments (capillary‐wetted and slaked) were applied to soil samples collected during the incubation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
142
0
9

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(160 citation statements)
references
References 6 publications
9
142
0
9
Order By: Relevance
“…These changes in the short term can be insignificant, yet SOC content for NT soil aggregates increased over time, consistent with the findings of Sainju et al (2008) and West and Post (2002). Stable macroaggregates are enriched in new SOC compared with unstable macroaggregates (Gale et al 2000), especially in relatively undisturbed systems like NT, where new root-derived intraaggregate particulate organic matter is important in stabilizing small macroaggregates. Although the differences in SOC and STN contents for soil with different tillage treatments were not significantly different (p < 0.05), all tillage systems' SOC and STN contents at the top 0 to 15 cm (0 to 6 in) depth were different from that for the baseline.…”
Section: Resultssupporting
confidence: 82%
“…These changes in the short term can be insignificant, yet SOC content for NT soil aggregates increased over time, consistent with the findings of Sainju et al (2008) and West and Post (2002). Stable macroaggregates are enriched in new SOC compared with unstable macroaggregates (Gale et al 2000), especially in relatively undisturbed systems like NT, where new root-derived intraaggregate particulate organic matter is important in stabilizing small macroaggregates. Although the differences in SOC and STN contents for soil with different tillage treatments were not significantly different (p < 0.05), all tillage systems' SOC and STN contents at the top 0 to 15 cm (0 to 6 in) depth were different from that for the baseline.…”
Section: Resultssupporting
confidence: 82%
“…This results in localized drying of the soil and cohesion of soil particles around the roots. The crucial role played by roots in the formation of waterstable aggregates has been recognized for some time [244], but only recently published results [116,208,257] have reported that roots are more important than shoots in the formation of aggregates and stabilization of aggregate-associated SOM (Tab. III).…”
Section: Model Of Interactions Between Aggregation and Biota Activitymentioning
confidence: 99%
“…This fine POM becomes increasingly encapsulated with minerals and microbial products, forming new microaggregates (53-250 µm) within the macroaggregates [10,116,150,207,230]. With active root growth stabilizing macroaggregates, intense biological activity (induced by root exudation) may also cause further encrustation of microbial products and mineral particles, forming microaggregates around root-derived POM [116].…”
Section: Model Of Interactions Between Aggregation and Biota Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Root growth and physiology also produced localised soil physical properties around the root, such as compaction (Misra et al, 1986). The drying of soil by roots together with the organic binding material produced in the rhizosphere is expected to enhance soil structural stability (Bowen and Rovira, 1991;Gale et al, 2000).…”
Section: Discussionmentioning
confidence: 99%